Serum and hair trace element levels in patients with epilepsy and healthy subjects: does the antiepileptic therapy affect the element concentrations of hair? - Ilhan, A; Uz, E; Kali, S; Var, A; Akyol, O (Wiley, 1999)
In this study, hair magnesium (Mg), zinc (Zn), copper (Cu), and manganese (Mn) levels, and serum Zn and Mg levels were measured by atomic absorption spectrophotometer in patients with epilepsy (n = 33) and healthy subjects (n = 21), and results obtained were statistically compared. The mean hair Cu, Mg, and Zn levels of epileptic patients were significantly lower than the levels of control subjects. There was no significant difference between epileptic patients and control subjects in respect to the mean Mn levels. Mean serum Mg levels in epileptic patients showed significant difference, but serum Zn levels were similar among both groups. When the effects of anticonvulsant therapy on Cu, Zn, Mn, and Mg in the hair, and Mg and Zn in the serum were analyzed in epileptics, there was no significant difference between the patients with or without therapy. Likewise, the mean trace element levels in epileptics showed no significant difference according to the type of antiepileptic drug and seizure, and gender. We suggest that the changed element status (Zn, Mg, and Cu) in hair may play an indicator role in the diagnosis of epileptic patients, fur J Neurol 6:705-709 (C) 1999 Lippincott Williams & Wilkins.
Keywords: epilepsy; hair; serum; copper; zinc; magnesium; manganese